Absolute decrease in regulatory T cells and low‐dose interleukin‐2 therapy: restoring and expanding regulatory T cells to treat systemic sclerosis: a 24‐week study. (2nd October 2022) - Yu, Zhen; Cheng, Hao; Ding, Tingting; Liang, Yuying; Yan, Chenglan; Gao, Chong; Wen, Hongyan
Abstract: Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular lesions, immunological alterations and tissue fibrosis. There is some evidence of an imbalance between T‐cell subsets in this disease. Interleukin (IL)‐2 is a cytokine that can regulate the activity of immune cells and there is evidence that low‐dose IL‐2 therapy can be used to treat immune diseases. Aim: To investigate the changes of peripheral lymphocyte subsets, especially T helper (Th)17 and regulatory T (Treg) cells and the effects of low‐dose IL‐2 therapy in patients with SSc. Methods: In total, 66 patients with SSc and 49 sex‐ and age‐matched healthy controls (HCs), were enrolled. The absolute numbers of peripheral lymphocyte subsets in these individuals were determined by flow cytometry. The 66 patients, were divided into 2 groups: 23 (the IL‐2 group) were treated with low‐dose (5.0 × 10 5  IU) IL‐2 by subcutaneous injection daily for 5 days combined with conventional therapy, while the remaining 23 patients received conventional therapy only. Results: Compared with HCs, the absolute numbers of peripheral T, CD4+ T, CD8+ T, natural killer and Treg cells were significantly lower in patients with SSc, with the most dramatic difference seen in both the absolute number and percentage of Treg cells in these patients, including new (previously untreated) cases, resulting in an imbalance (elevated ratio) between Th17 and Treg cells. At Week 24 after commencement of IL‐2 treatment, Treg cells were markedly increased and tended to restore the balance of Th17 to Treg cells compared with baseline. Erythrocyte sedimentation rate, C‐reactive protein, modified Rodnan Skin Score and visual analogue scale score were significantly decreased in both the IL‐2 and non‐IL‐2 groups, indicating disease improvement. Notably, compared with those in the non‐IL‐2 group, patients treated with IL‐2 had greater improvement. Conclusion: Our study showed that the absolute numbers of peripheral Treg cells together with total T, CD4+ T, CD8+ T and NK is significantly decreased, leading to an imbalance of Th17 to Treg cells in patients with SSc, and that low‐dose IL‐2 treatment could restore the balance of the two immune cells and reduce disease activity without obvious adverse effects. Abstract : The absolute numbers of peripheral regulatory T (Treg) and natural killer cell subsets are significantly decreased in SSc, leading to an imbalance of T helper (Th)17 Treg cells in these patients. After therapy with low‐dose interleukin (IL)‐2, the patients improved in line with the rebalancing of the Th17/Treg ratio. Low‐dose IL‐2 treatment could restore the balance of the two types of immune cell and reduce disease activity without obvious adverse effects.